Student perceptions of a virtual learning environment for a problem-based learning undergraduate medical curriculum. - de Leng BA; Dolmans DH; Muijtjens AM; van der Vleuten CP (Medical Education, 2006)
OBJECTIVE: To investigate the effects of a virtual learning environment (VLE) on group interaction and consultation of information resources during the preliminary phase, self-study phase and reporting phase of the problem-based learning process in an undergraduate medical curriculum. METHODS: A questionnaire was administered to 355 medical students in Years 1 and 2 to ask them about the perceived usefulness of a virtual learning environment that was created with Blackboard for group interaction and the use of learning resources. RESULTS: The students indicated that the VLE supported face-to-face interaction in the preliminary discussion and in the reporting phase but did not stimulate computer-mediated distance interaction during the self-study phase. They perceived that the use of multimedia in case presentations led to a better quality of group discussion than if case presentations were exclusively text-based. They also indicated that the information resources that were hyperlinked in the VLE stimulated the consultation of these resources during self-study, but not during the reporting phase. CONCLUSIONS: Students indicated that the use of a VLE in the tutorial room and the inclusion of multimedia in case presentations supported processes of active learning in the tutorial groups. However, if we want to exploit the full potential of asynchronous computer-mediated communication to initiate in-depth discussion during the self-study phase, its application will have to be selective and deliberate. Students indicated that the links in the VLE to selected information in library repositories supported their learning.